Nonlinear multivariable tracking control: application to an ethanol process. (28th March 2019) - Fernández, Maria Cecilia; Pantano, María Nadia; Machado, Ricardo Antonio F.; Ortiz, Oscar Alberto; Scaglia, Gustavo J.E.
In this paper, a controller based on linear algebra for a fed-batch ethanol production process is proposed. It involves finding feed rate profiles (control actions obtained as a linear equations system solution) in order to make the system follow predefined concentration profiles. A Monte Carlo experiment is used for controller tuning. Moreover, several tests (adding parametric uncertainty, perturbations in the control action and in the initial conditions) are carried out so as to evaluate the controller performance. A comparison with other controller is made and the demonstration of the error convergence is included.